Linguistic Methods of Implementing a Communicative Strategy of Self-Defense in American Political Discourse - Ya. Y. Khlopotunov (Дискурс профессиональной коммуникации, 2022)
This paper aims to study linguistic techniques of the communicative strategy of self-defense as one of the confrontational communicative strategies of American political discourse. The relevance of the study is revealed in the transformation of modern American political rhetoric, the consequence of which is the intensification of conventionally destructive elements in American political rhetoric and the predominance of subjective-negative modality units in political speech. The communicative strategy of self-defense allows the communicant to divert negative information from themselves and move from a defensive position to an attack. The author analyzes various tactical ways of implementing a communicative strategy of self-defense, which include justification, challenging, retaliatory criticism (counter-accusation), indignation, and opposition. They include several linguistic means (lexical units with a negative evaluation, deictic constructions, spoken words, lexical repetitions, personal pronouns, gradation, etc.). This article examines the roles of participants in the speech act of confrontation. The following models of speech behavior can be distinguished: offensive (attack, provocation), defense (self-defense, reaction to provocation), and evaluation (based on observation of the conflict). Thanks to the implementation of the communicative strategy of self-defense, the transition of the communicant from defense to offensive is possible.